2012
DOI: 10.1063/1.4726106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polarity on carrier transport in semipolar (2021¯) and (202¯1) multiple-quantum-well light-emitting diodes

Abstract: We investigate the influence of polarity on carrier transport in single-quantum-well and multiple-quantum-well (MQW) light-emitting diodes (LEDs) grown on the semipolar (20 21) and (2021) orientations of free-standing GaN. For semipolar MQW LEDs with the opposite polarity to conventional Ga-polar c-plane LEDs, the polarization-related electric field in the QWs results in an additional energy barrier for carriers to escape the QWs. We show that semipolar (2021) MQW LEDs with the same polarity to Ga-polar c-plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…18 The decrease in R d correlates well with the reduction in p-GaN thickness, given that the bulk resistivity of ITO is several orders of magnitude lower than p-GaN. The difference in voltage between the blue and green LDs is consistent with previously observed increased voltage for longer wavelength ð20 21Þ MQW active regions, 19 along with reduced p-GaN growth temperature and increased p-GaN thickness of the green LD. The overall high voltage is likely related to un-optimized contacts and doping profiles.…”
supporting
confidence: 84%
“…18 The decrease in R d correlates well with the reduction in p-GaN thickness, given that the bulk resistivity of ITO is several orders of magnitude lower than p-GaN. The difference in voltage between the blue and green LDs is consistent with previously observed increased voltage for longer wavelength ð20 21Þ MQW active regions, 19 along with reduced p-GaN growth temperature and increased p-GaN thickness of the green LD. The overall high voltage is likely related to un-optimized contacts and doping profiles.…”
supporting
confidence: 84%
“…6,7 As in the case of polar or non-polar nitride analysis, 8 X-ray diffraction (XRD) can be used on semi-polar layers to determine the alloy composition and the thickness of multiple quantum wells (MQWs) and other thin epilayers. In semi-polar samples, tilt 9 is commonly observed with epilayers growing at an angle from the template, leading to partial relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…The need to manage piezoelectric polarization in InGaN/GaN superlattices 29 has led to attempting to synthesize devices on substrates with non-polar and semi-polar crystal orientations. 30,31,32,33 However, the output powers at high injection current of these devices currently do not outperform the best devices grown on (0001) planes (c-planes). 14,34, 35 Crutchley et al 36 showed experimentally that there appears to be a linear correlation between the change in internal field and the reduction of the optical effici-FIGURE 5.…”
Section: Iii-n Light Emitting Diodesmentioning
confidence: 99%